Cerebral tissue oxygen saturation and its potential relationship with neurodevelopmental delay in pediatric liver transplant recipients - Fan, Yichen; Pan, Qianling; Su, Henghua; Pu, Zhongchan; Zhu, Linjie; Qi, Bo; Su, Diansan; Yang, Liqun; Huang, Dan; Yu, Weifeng (Frontiers in Pediatrics, 2025)
ObjectiveTo discover the potential association between diminished intraoperative average SctO2 levels and postoperative neurodevelopmental delays among patients after pediatric living-donor liver transplantation.Study designPatients undergoing living-donor liver transplantation were recruited for this trial. The neurodevelopment status of patients was assessed using the Ages Stages Questionnaires. The primary outcome was the occurrence of neurodevelopmental delay among patients at different intervals following pediatric liver transplantation. Secondary outcomes included the duration of mechanical ventilation, rates of re-intubation, length of ICU stay, postoperative hospitalization, and intraoperative comparisons of mean arterial pressure (MAP), arterial partial pressure of oxygen (PaO2), arterial partial pressure of carbon dioxide (PaCO2), and hemoglobin (Hb) concentration.ResultsA total of 119 patients were included in the statistical analysis and assigned to high saturation group (HS) and low saturation group (LS) according to the average intraoperative cerebral tissue oxygen saturation values. Following adjustment for PELD scores, significant differences between the two groups were observed for the incidence of neurodevelopmental delay in communication at 1 and 3 months follow-up (P = 0.019 and P = 0.020, respectively), fine motor at six months follow-up (P = 0.014), and problem-solving abilities at one year follow-up (P = 0.047). Moverover, the length of ICU stay (P = 0.009) and postoperative hospitalization (P = 0.029) in LS group were also significant prolonged.ConclusionThis prospective observational study revealed that the patients with low average SctO2 values were more predisposed to experiencing postoperative neurodevelopment delays, suggesting a potential association between decreased average SctO2 and neurodevelopmental delay.